Improving Students’ Plant Literacy in Plant Classification through Mobile Learning Integrated with Experiential Learning - Aris Sunandar; Kusnadi Kusnadi; Amprasto Amprasto (CV. Dharma Samakta Edukhatulistiwa, 2026)
This study examined how integrating mobile learning with experiential activities can improve high school students’ understanding of plant classification. Using a quasi-experimental pretest–posttest control group design, 76 tenth-grade students at SMAN 1 Tukdana, Indonesia, were evenly split into experimental and control groups. The experimental group learned through mobile tools such as PlantNet, iNaturalis, Google Lens, LMS, and Digiventory within an experiential learning framework, while the control group received traditional instruction. Plant literacy was assessed with a 30-item multiple-choice test focused on nominal, functional, structural, and dimensional knowledge. Data analysis involved N-Gain, independent t-tests, and Cohen’s d. Results showed that the experimental group achieved significantly higher Normalized gains (N-Gain = 60.21%) than the control group (21.91%), with a significant difference (p < 0.05) and a very large effect size (d = 2.07). These results suggest that combining mobile and experiential learning methods effectively enhances students’ plant literacy by encouraging actively and contextual learning. This approach is recommended for biology education and for further research across different settings.